2013
DOI: 10.1021/jp4098292
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Kinetic and Thermodynamic Landscape of Formaldehyde Oligomerization under Neutral Conditions

Abstract: Density functional theory calculations, including Poisson-Boltzmann implicit solvent and free energy corrections, are applied to study the thermodynamic and kinetic free energy landscape of formaldehyde oligomerization up to the C4 species in aqueous solution at pH 7. Oligomerization via C-O bond formation leads to linear polyoxymethylene (POM) species, which are the most kinetically accessible oligomers and are marginally thermodynamically favored over their oxane ring counterparts. On the other hand, C-C bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(95 citation statements)
references
References 51 publications
2
92
1
Order By: Relevance
“…The reasons for this, in conjunction with using half the gas phase entropy, are discussed further in Supplementary Information. On the other hand, our protocol performs well in calculating the relative free energies of stable species, typically within 0.5 kcal/mol of experimental results, [9][10]12 or an uncertainty of within a factor of 2.3 in terms of equilibrium constant ratios. …”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…The reasons for this, in conjunction with using half the gas phase entropy, are discussed further in Supplementary Information. On the other hand, our protocol performs well in calculating the relative free energies of stable species, typically within 0.5 kcal/mol of experimental results, [9][10]12 or an uncertainty of within a factor of 2.3 in terms of equilibrium constant ratios. …”
Section: Methodsmentioning
confidence: 84%
“…The activation barriers compared to experiment are reasonable but the agreement is not as close, and our protocol overestimates the barrier by 2-3 kcal/mol. [9][10] The barriers are calculated in reference to the separated reactants rather than a pre-associated complex. The reasons for this, in conjunction with using half the gas phase entropy, are discussed further in Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to assess the extensiveness of our protocol we compared our reaction network with one obtained from a manual exploration. 103 Within the bounds preset for the present exploration, each intermediate and reaction path identified in a limited manual exploration by Kua et al 103 can be found in our reaction network. Figure 6: Reaction network generated from formaldehyde, glycolaldehyde, and water (the last not shown explicitly) consisting of reactions with activation barriers below 85 kJ/mol.…”
Section: Reaction Networkmentioning
confidence: 95%
“…4. It represents a possible mechanism for the rst steps of the formose reaction as described by Kua et al 37 and comprises six chemical species and ve reaction pairs (ten elementary reactions Ri). We obtained all free energies in single-point calculations as described in the ESI.…”
Section: Kinetic Simulation Algorithmmentioning
confidence: 99%